KUALITAS LAYANAN DONGENG ANAK DAN REMAJA KELILING (DARLING) DI DINAS PERPUSTAKAAN DAN KEARSIPAN PROVINSI JAWA TIMUR - Kharisma Sintya Sandea; Susi Hardjati (Jurnal Penelitian Administrasi Publik, 2019)
In carrying out its functions, the library is one of the government institutions that are required to provide public services. Service is the most important element in the process of library activities. Therefore the library is required to provide a quality service to fulfill community needs because good library services will be able to attract the community. Through the Children and Teenagers Fairy Tale service (DARLING) is a tangible proof of public service innovation that can meet people's needs through children's stories. The existence of these services is expected to be able to generate interest in reading children from an early age. It is necessary to improve the quality of public services because it is a real attitude of the government in carrying out the performance, responsibilities, and commitment of service provider organizations in relation to the needs, demands and interests of the community. The government makes efforts to improve the quality of public services with various strategies in the hope of future changes. This research is a qualitative descriptive study with data collection techniques in the form of observation, interviews, and documentation. Meanwhile, the focus of this research can be seen from the dimensions of Tangible, Reliable, Responsiveness, Assurance, and Empathy. The results of the study show that the quality of the Aroundland Children and Youth Tale (DARLING) service in the Library and Archives Service of East Java Province has been well implemented, so that in the process of service community satisfaction can be achieved. Keywords: Public Services, Service Quality